Nonsurgical Endodontic Retreatment of Advanced Inflammatory External Root Resorption Using Mineral Trioxide Aggregate Obturation - Shivani Utneja; Gaurav Garg; Shipra Arora; Sangeeta Talwar (Hindawi Limited, 2012)
Inflammatory external root resorption is one of the major complications after traumatic dental injury. In this case report, we describe treatment of a maxillary central incisor affected by severe, perforating external root resorption. An 18-year-old patient presented with a previously traumatized, root-filled maxillary central incisor associated with pain and sinus tract. Radiographic examination revealed periradicular lesion involving pathologic resorption of the apical region of the root and lateral root surface both mesially and distally. After removal of the root canal filling, the tooth was disinfected with intracanal triple antibiotic paste for 2 weeks. The antibiotic dressing was then removed, and the entire root canal was filled with mineral trioxide aggregate. The endodontic access cavity was restored with composite resin. After 18 months, significant osseous healing of the periradicular region and lateral periodontium had occurred with arrest of external root resorption, and no clinical symptoms were apparent.